PEMBUATAN ADSORBEN DARI KULIT BATANG JAMBU BIJI (Psidium guajava L.) UNTUK MENJERAP LOGAM TEMBAGA (Cu) DAN NIKEL (Ni) PADA LIMBAH CAIR INDUSTRI PELAPISAN LOGAM - Setiaty Pandia, Muhammad Ferdiyansyah, Febri Maihendra (Universitas Sumatera Utara, 2017)
This research aims to study the effect of adsorption time, adsorption temperature, pH, and the ratio of raw materials with nitric acid in the manufacture of bark guava adsorbent in reducing the metals content of copper (Cu) and nickel (Ni) in the metal wastewater industry. Materials used include, among others, industrial metal coating wastes, guava stem bark, nitric acid, and aquadest. Initially the bark of guava stalk was cleansed and mashed 70-80 size, then activated with 4 N nitric acid (HNO3) solution with a variation in the ratio of bark the guava : nitric acid is 1:1; 1:2; and 1;3 g/mL were heated at 80oC for 120 minutes. The adsorbent is then dried in the oven at 110oC for 120 minutes. Adsorbent with the highest iodine number analysis results was used in the adsorption process of Cu (II) Ni(II) metals, wherein the adsorbent mass used was 2 grams in 150 ml of metallic industry liquid waste, 70 rpm stirrer speed, variation of adsorption times are 60, 90, and 120 minutes, variation of adsorption temperatures are 35oC, 45oC, and 55oC, and variation of adsorption pH are 2, 7, and 12. The result showed that the ratio of bark of guava stem: the best nitric acid was 1: 3 g/mL with iodine number of 313,020 mg/g. Based on Liquid Waste Quality Standard for Industrial Activity (KepMen LH 51/1995), the copper and nickel content in liquid waste should not exceed 3 mg/L and 3 mg/L for metal coating industry. From the results of adsorption process that has been done, got the optimum condition of adsorption of copper metal that is at 60 minutes, temperature 35oC, and pH 7 and obtained the efficiency of adsorption equal to 69,1540%, and nickel metal that is at 60 minutes, temperature 35oC, and pH 7and obtained the efficiency of adsorption equal to 75,1700%, where the result of adsorption the Cu2+ and Ni2+ metal ions are 2,8077 mg/L and 4,1100 mg/L.